2001
DOI: 10.1038/35051537
|View full text |Cite
|
Sign up to set email alerts
|

Observation of shear-induced nematic–isotropic transition in side-chain liquid crystal polymers

Abstract: Flow-induced phase transitions are a fundamental (but poorly understood) property of non-equilibrium systems, and are also of practical importance for tuning the processing conditions for plastics, petroleum products, and other related materials. Recognition that polymers may exhibit liquid crystal properties has led to the discovery of the first tailored side-chain liquid crystal polymers (SCLCPs), which are formed by inserting a spacer between the main polymer chain and the lateral mesogen liquid-crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
98
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 22 publications
8
98
1
1
Order By: Relevance
“…A proper understanding of the mesogenebackbone interaction is one of the key issues in order to develop the SCPLCs into useful materials. Experimentally the determination of this interaction is an open question [20], and only recently neutron scattering experiments [10,21,22] have shown that the polymeric backbone configuration can indeed be correlated to the local mesogene director.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A proper understanding of the mesogenebackbone interaction is one of the key issues in order to develop the SCPLCs into useful materials. Experimentally the determination of this interaction is an open question [20], and only recently neutron scattering experiments [10,21,22] have shown that the polymeric backbone configuration can indeed be correlated to the local mesogene director.…”
mentioning
confidence: 99%
“…This aligned material is technologically interesting because of its strong birefringence and forms an ideal target for further scientific studies like x-ray or neutron scattering experiments. In comparison with other alignment techniques [7][8][9][10][11], magnetic alignment has several advantages, since the field exerts a well-defined, contact free, torque force on all molecules, and can therefore be used for thin films as well as bulk samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A simple closure condition for passive hard rods [46] is Q ∼ (PP) + , where A + with components A + ij = (A ij + A ji − δ ij A kk )/2 denotes the symmetric traceless part of tensor A in 2D. However, this commonly used closure condition does not account for the fact that active microswimmers permanently impose stress on the ambient fluid which feeds back into the orientational order, analogous to the shear-induced isotropicnematic transition in liquid crystals [47][48][49][50]. To derive a selfconsistent closure condition, we multiply Eq.…”
mentioning
confidence: 99%
“…Les régimes de relaxation après élongation comme la reptation sont profondément modifiés par l'état cristal liquide [1 ]. Une phase nématique différente, induite par le cisaillement, a été observée par rhéo-DNPA [12] (bas de la Figure 19). 6.…”
Section: Autres Architectures Copolymeres Polymeres Cristaux Liquidesunclassified